Analisis Implementasi Aplikasi Pajak CoreTax dalam Meningkatkan Kepatuhan dan Efisiensi Pelaporan Pajak di Indonesia - Teguh Purnomo; Amin Sadiqin; Rizki Arvita (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2025)
This research aims to analyse the implementation of the CoreTax tax application in improving taxpayer compliance and tax reporting efficiency in Indonesia. Using a qualitative approach, this study evaluates the effectiveness of the CoreTax application through in-depth interviews with users and a review of secondary data. The results show that CoreTax simplifies the tax reporting process through automation features, data integration, and a comprehensive user guide. In addition, the implementation of this application has a positive impact on improving taxpayer compliance by reducing reporting errors and speeding up the filing process. However, the research also found some constraints, such as low levels of technological literacy and the need for additional training for certain users. Strategic recommendations are provided to improve the adoption and performance of the CoreTax application going forward.